Effects of Bisphenols A, AF, and S on Endochondral Ossification and the Transcriptome of Murine Limb Buds. (29th November 2021) - Iskandarani, Lama; McHattie, Tessa; Robaire, Bernard; Hales, Barbara F
Abstract: Bisphenols are a family of chemicals commonly used to produce polycarbonate plastics and epoxy resins. Exposure to bisphenol A (BPA) is associated with a variety of adverse effects; thus, many alternatives to BPA, such as bisphenol AF (BPAF) and bisphenol S (BPS), are now emerging in consumer products. We have determined the effects of 3 bisphenols on endochondral ossification and the transcriptome in a murine limb bud culture system. Embryonic forelimbs were cultured in the presence of vehicle, BPA, BPAF, or BPS. BPA (≥ 10 μM), BPAF (≥ 1 μM), and BPS (≥ 50 μM) reduced the differentiation of hypertrophic chondrocytes and osteoblasts. Chondrogenesis was suppressed by exposure to ≥ 50 μM BPA, ≥ 5 μM BPAF, or 100 μM BPS and osteogenesis was almost completely arrested at 100 μM BPA or 10 μM BPAF. RNA sequencing analyses revealed that the total number of differentially expressed genes increased with time and the concentration tested. BPA exposure differentially regulated 635 genes, BPAF affected 554 genes, whereas BPS affected 95 genes. Although the genes that were differentially expressed overlapped extensively, each bisphenol also induced chemical-specific alterations in gene expression. BPA- and BPAF-treated limbs exhibited a downregulation of Rho-specific guanine nucleotide dissociation inhibitor (RhoGDI) signaling genes. Exposure to BPA and BPS resulted in the upregulation of key genes involved in cholesterol biosynthesis, whereas exposure to BPAF induced an upregulation of genes involved in bone formation and in the p53 signaling pathway. These data suggest that BPAF may be more detrimental to endochondral ossification than BPA, whereas BPS is of comparable toxicity to BPA.